Development of DCS SCADA Teaching Module on A Pid-Based Water Level Control Case Using Labview and Factory I/O - Lutfi; Sukriyah Buwarda (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2022)
The DCS SCADA course is one of the latest courses for the 2022 curriculum at Politeknik ATI Makassar. This course has case study-based learning from the industrial world and involves very expensive instrumentation devices for Real Plant, so a Teaching Module with factory i/o was created. This research aims to develop a DCS SCADA Teaching Module based on the Water Level Control case using Labview and Factory I/O. The virtual plant uses a water tank with instruments consisting of two control valves, namely the fill valve and the discharge valve, and two transducers, namely the level meter and the flow meter. To connect the factory I/O to NI Labview, the open protocol Modbus Ethernet is used. Based on the testing results, the calibration for the level measurement has an accuracy of 99.59% and a precision of 0.69 % with the interpolation y = 0.301x -0.536 for a 100 % correlation. For the system response with SP = 150 without disturbance, the PID parameters should be set to Kp = 25, Ti = 0.1, and Td = 0 with a system response consisting of Rise Time = 396 seconds, no Overshoot, Settling Time = 430 seconds, and Steady state error = 0.566 cm. For the system response with SP = 150 with a DV = 50 percent disturbance, the PID parameters should be set to Kp = 25, Ti = 0.1, and Td = 0 with a system response consisting of Rise Time = 382 seconds, no Overshoot, Settling Time = 462 seconds, and Steady state error = 1.469 cm.